Methodology of Selecting Optimal Fare System for Public Transport of Passengers - Popović, Vladimir Dragan; Gladović, Pavle; Miličić, Milica; Stanković, Milan (Promet - Traffic&Transportation, 2018)
According to the European Committee (EC) on Transport, the future road transport strategy lies in creating a strong road transport sector which is based on a well-functioning internal market, fair competition and workers’ rights, decarbonization, and use of digital technologies. Urban and suburban passenger transportation systems, according to the principles of the EC, have a key role in achieving the goal of sustainable development and sustainable transport in cities. The fare, ticketing, and payment modes have a significant impact on public urban transport systems, primarily in terms of collecting transport service fees, and represent the basic source of financing of such systems, in addition to subsidies and grants from city budgets. This paper presents the selection methodology of the optimal fare system for urban public transport, applicable for all cities with an organized public city passenger transport (PCPT) system. Based on the established criteria with respect to setting tariff limits and fare systems, passenger demand, and the enterprise organizing the transport, the tariff system was selected. The presented method is that of multi- criteria optimization of the tariff system with numerical results on the example of the City of Novi Sad.